Rancang Bangun Aplikasi Media Pembelajaran Perakitan dan Perawatan pada Sistem Komputer Berbasis Android - Mohammad Yaqin Amirullah; Nuzul Hikmah; Ary Analisa Rahma (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2020)
Teaching and learning is basically a process of educational interaction between teacher and student. Learning media become a very important part of the learning process. Therefore it is necessary to find an attractive learning media for students one of them is interactive learning media. Computer learning is one of the basic competency standards taught to students in vocational high schools. Based on observations at the Vocational High School Zainul Hasan Genggong Genggong with the speaker Mr. Mohammad Saleh, S.Kom as a teacher in the Vocational Basic Computer and Network Engineering, he said that the teacher still uses the delivery of material by whiteboard and also uses projector presentation aids using the projector power point slides especially the Vocational Basic Computer and Network Engineering lessons. Therefore it is necessary to find an attractive learning media for students one of them is interactive learning media. Interactive learning media has several elements such as text, audio, video and images, so that it is more interesting to students and students feel happy in learning compared to the way that is still very conventional. The research method used is research development with the stages of study of literature, observation, data collection, system analysis, system design, application implementation, application testing. For the implementation stage, an application has been made as a learning medium that can be accessed using an Android smartphone with a user friendly display, including pictures and videos. Based on the results of testing using blackbox testing and testing in various android platforms learning applications run well in accordance with the results expected by the user.